UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LAGU DAERAH MENGGUNAKAN MODEL EXAMPLES AND NON-EXAMPLES - Marvella, Agnes; Djau, Nurmila; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to improve student learning outcomes in the material characteristics and functions of regional songs using Examples and Non-Examples models. The theory used in this study is Learning and Learning, Learning Outcomes, Understanding Examples and Non-Examples of Models, Strengths and Disadvantages of Examples and Non-Examples Models. The form of this research is classroom action research with procedures for planning, action, observation, and reflection. The research subjects were students of class VIII B, SMP Negeri 25 North Pontianak, amounting to 36 people. Data analysis techniques collected in the form of student learning outcomes data in the material characteristics and functions of folk songs. This research was conducted in two cycles, namely cycle I and II. These results can also be seen from the percentage of completeness in the first cycle, which is 47.2%. In the second cycle student learning outcomes on material characteristics. And the function of folk songs is very good, from cycle I to cycle II, 47.2% to 86.11%. Thus, it can be concluded that the concepts of Examples and Non-Examples models can improve student learning outcomes in the material characteristics and functions of folk songs.Â Keywords: Examples and Non-Examples Models, Learning Outcomes, Regional SongsÂ